Meta-omic signatures of microbial metal and nitrogen cycling in marine oxygen minimum zones - Glass, Jennifer B.; Kretz, Cecilia B.; Ganesh, Sangita; Ranjan, Piyush; Seston, Sherry L.; Buck, Kristen N.; Landing, William M.; Morton, Peter L.; Moffett, James W.; Giovannoni, Stephen J.; Vergin, Kevin L.; Stewart, Frank J. (Frontiers in Microbiology, 2015)
Iron (Fe) and copper (Cu) are essential cofactors for microbial metalloenzymes, but little is known about the metalloenyzme inventory of anaerobic marine microbial communities despite their importance to the nitrogen cycle. We compared dissolved O2, NO3-, NO2-, Fe and Cu concentrations with nucleic acid sequences encoding Fe and Cu-binding proteins in 21 metagenomes and 9 metatranscriptomes from Eastern Tropical North and South Pacific oxygen minimum zones and 7 metagenomes from the Bermuda Atlantic Time-series Station. Dissolved Fe concentrations increased sharply at upper oxic-anoxic transition zones, with the highest Fe:Cu molar ratio (1.8) occurring at the anoxic core of the Eastern Tropical North Pacific oxygen minimum zone and matching the predicted maximum ratio based on data from diverse ocean sites. The relative abundance of genes encoding Fe-binding proteins was negatively correlated with O2, driven by significant increases in genes encoding Fe-proteins involved in dissimilatory nitrogen metabolisms under anoxia. Transcripts encoding cytochrome c oxidase, the Fe- and Cu-containing terminal reductase in aerobic respiration, were positively correlated with O2 content. A comparison of the taxonomy of genes encoding Fe- and Cu-binding vs. bulk proteins in OMZs revealed that Planctomycetes represented a higher percentage of Fe genes while Thaumarchaeota represented a higher percentage of Cu genes, particularly at oxyclines. These results are broadly consistent with higher relative abundance of genes encoding Fe-proteins in the genome of a marine planctomycete vs. higher relative abundance of genes encoding Cu-proteins in the genome of a marine thaumarchaeote. These findings highlight the importance of metalloenzymes for microbial processes in oxygen minimum zones and suggest preferential Cu use in oxic habitats with Cu > Fe vs. preferential Fe use in anoxic niches with Fe > Cu.